Adaptive Changes in the Sensitivity of the Dorsal Raphe and Hypothalamic Paraventricular Nuclei to Acute Exercise, and Hippocampal Neurogenesis May Contribute to the Antidepressant Effect of Regular Treadmill Running in Rats - Nishii, Ayu; Amemiya, Seiichiro; Kubota, Natsuko; Nishijima, Takeshi; Kita, Ichiro (Frontiers in Behavioral Neuroscience, 2017)
Increasing clinical evidence suggests that regular physical exercise can prevent or reduce the incidence of stress-related psychiatric disorders including depressive symptoms. Antidepressant effect of regular exercise may be implicated in monoaminergic transmission including serotonergic transmission, activation of the hypothalamic-pituitary-adrenal (HPA) axis, and hippocampal neurogenesis, but few general concepts regarding the optimal exercise regimen for stimulating neural mechanisms involved in antidepressant properties have been developed. Here, we examined how 4 weeks of treadmill running at different intensities (0, 15, 25 m/min, 60 min/day, 5 times/week) alters neuronal activity in the dorsal raphe nucleus (DRN), which is the major source of serotonin neurons in the central nervous system, and the hypothalamic paraventricular nucleus (PVN), in which corticotropin-releasing factor neurons initiate the activation of the HPA axis, during one session of acute treadmill running at different speeds (0, 15, 25 m/min, 30 min) in male Wistar rats, using c-Fos immunohistochemistry. We also examined neurogenesis in the hippocampus using immunohistochemistry for doublecortin (DCX) and assessed depressive-like behavior using the forced swim test after regular exercise for 4 weeks. In the pre-training period, acute treadmill running at low speed, but not at high speed, increased c-Fos positive nuclei in the DRN compared with the sedentary control. The number of c-Fos positive nuclei in the PVN during acute treadmill running was increased in a running speed-dependent manner. Regular exercise for 4 weeks, regardless of the training intensity, induced an enhancement of c-Fos expression in the DRN during not only low-speed but also high-speed acute running, and generally reduced c-Fos expression in the PVN during acute running compared with pre-training. Furthermore, regular treadmill running for 4 weeks enhanced DCX immunoreactivity in the hippocampal dentate gyrus, and resulted in decreased depressive-like behavior, regardless of the training intensity. These results suggest that long-term repeated exercise, regardless of the training intensity, improves depressive-like behavior through adaptive changes in the sensitivity of DRN and PVN neurons to acute exercise, and hippocampal neurogenesis.